Toxicity of treated bilge water: The need for revised regulatory control. Issue 2 (30th January 2017) - Tiselius, Peter; Magnusson, Kerstin
Abstract: Water accumulating in the bottom of ships (bilge water), contains a mixture of oil, detergents and other compounds from on board activities. To evaluate ecological effects of released bilge water the chemical composition and toxicity of treated bilge water from seven passenger ships was analysed. The oil content was below 15 mg L − 1, the threshold for legal discharge, in all but one ship. Still, significant reductions in feeding and reproduction of Acartia tonsa were found after 48 h exposure in dilutions with 2.5–5% of bilge water. Mortality was significant at dilutions of 5–10% in 4 of the 5 bilge water samples. Surfactants were the most significant contributor to the toxicity on copepod vital rates and survival. Toxicity was also tested with Microtox where an EC50 was found at dilutions between 4.3% and 52%. The results show that ecological effects might occur also in diluted suspensions of bilge water. Highlights: Copepod feeding and reproduction were reduced in dilutions of 2.5–5% of bilge water. Mortality was significant at dilutions of 5–10% bilge water. Surfactants were the most significant contributor to the toxicity. Microtox assays revealed an EC50 between 4.3% and 52%. Ecological effects occur in diluted suspensions of bilge water.